Discourse and Anti-Communist Ideology in Lima’s Popular Press During the 2021 Presidential Runoff - Caballero Rojas, Gerardo Alonso (2023)
This article studies the role of the sensationalist popular press during the campaign for the second electoral round carried out in Peru between April and June 2021. For this, the journalistic discourse on the front pages of the newspapers Trome and Ojo is analyzed, which are the two popular newspapers of the largest media conglomerate in the country, the El Comercio Group. The study identifies in the discourse on the covers of Trome and Ojo—whose agendas are traditionally devoted to police news, entertainment and sports—the presence of what Noam Chomsky and Edward S. Herman (1988/1995) call anti-communist ideology. Through it, they sought to associate candidate Pedro Castillo with “communism” or “chavismo”, and present him as the worst of evils. The discourse of these popular newspapers was oriented to associate their idea of communism with terrorism, violence and hatred, and, at the same time, contrast it with those of democracy, peace and freedom. Furthermore, both Trome and Ojo repeatedly disqualify Pedro Castillo’s economic proposals and associate their own idea of communism with poverty and hunger.